Rationale, design, demographics and baseline characteristics of the randomized, controlled, Phase 2b SAPPHIRE study of verinurad plus allopurinol in patients with chronic kidney disease and hyperuricaemia. Issue 8 (12th August 2021) - Heerspink, Hiddo J L; Stack, Austin G; Terkeltaub, Robert; Greene, Tom A; Inker, Lesley A; Bjursell, Magnus; Perl, Shira; Rikte, Tord; Erlandsson, Fredrik; Perkovic, Vlado
ABSTRACT: Background: Verinurad is a human uric acid (UA) transporter (URAT1) inhibitor known to decrease serum UA (sUA) levels and that may reduce albuminuria. In a Phase 2a study (NCT03118739), treatment with verinurad + febuxostat lowered urine albumin-to-creatinine ratio (UACR) at 12 weeks by 39% (90% confidence interval 4–62%) among patients with Type 2 diabetes mellitus, hyperuricaemia and albuminuria. The Phase 2b, randomized, placebo-controlled Study of verinurAd and alloPurinol in Patients with cHronic kIdney disease and hyperuRicaEmia (SAPPHIRE; NCT03990363) will examine the effect of verinurad + allopurinol on albuminuria and estimated glomerular filtration rate (eGFR) slope among patients with chronic kidney disease (CKD) and hyperuricaemia. Methods: Adults (≥18 years of age) with CKD, eGFR ≥25 mL/min/1.73 m 2, UACR 30–5000 mg/g and sUA ≥6.0 mg/dL will be enrolled. Approximately 725 patients will be randomized 1:1:1:1:1 to 12, 7.5 or 3 mg verinurad + allopurinol, allopurinol or placebo. An 8-week dose-titration period will precede a 12-month treatment period; verinurad dose will be increased to 24 mg at Month 9 in a subset of patients in the 3 mg verinurad + allopurinol arm. The primary efficacy endpoint the is change from baseline in UACR at 6 months. Secondary efficacy endpoints include changes in UACR, eGFR and sUA from baseline at 6 and 12 months. Conclusions: This study will assess the combined clinical effect of verinurad + allopurinol on kidney function in patients with CKD, hyperuricaemia and albuminuria, and whether this combination confers renoprotection beyond standard-of-care. Graphical Abstract: